Beyond co‐operation and competition: Anglo‐French relations, connected histories of decolonization and Rhodesia's Unilateral Declaration of Independence, 1965–80 - Warson, Joanna (Historical research, 2015)
This article analyses Anglo‐French relations with regard to Rhodesia's Unilateral Declaration of Independence (U.D.I.). It highlights how long‐standing ideas about co‐operation and competition shaped British and French views of each other in the Rhodesian context, as well as French policies towards U.D.I. The article then moves beyond the dichotomy between alliance and acrimony, identifying other themes that informed Anglo‐French relations in this rebellious British colony. By exploring interaction between Britain, France and Rhodesia, it challenges the binaries that dominate the study of the end of European colonial rule in the twentieth century, offering instead a connected history of decolonization.